Island of lost souls [videorecording (DVD)] - Kenton, Erle C., 1896-1980; Laughton, Charles, 1899-1962; Arlen, Richard, 1900-1976; Lugosi, Bela, 1882-1956; Hyams, Leila, 1905-1977; Burke, Kathleen, 1913-1980; Wells, H. G. (Herbert George), 1866-1946 (Criterion collection, 2011)
Charles Laughton plays a mad doctor conducting ghastly genetic experiments on a remote island in the South Seas, much to the fear and disgust of the shipwrecked sailor who finds himself trapped there.